2020
DOI: 10.1177/1756286420909991
|View full text |Cite
|
Sign up to set email alerts
|

Different risk factors in identical features of intracranial atherosclerosis plaques in the posterior and anterior circulation in high-resolution MRI

Abstract: Background: We constructed a high-volume registry to identify whether risk factors of intracranial atherosclerotic plaque (ICAP) features differ in the posterior and anterior circulation in patients with symptomatic intracranial atherosclerotic stenosis (ICAS) investigated by high-resolution magnetic resonance imaging (HRMRI). Methods: The registry was constructed for patients with symptomatic ICAS who underwent HRMRI for culprit plaques. ICAP-vulnerable features included positive remodelling, diffuse distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
3
9
2
Order By: Relevance
“…Compared with non-diabetic patients, diabetic patients had a signi cantly higher incidence of plaque enhancement, longer maximum plaque length, greater maximum plaque wall thickness, and increased luminal stenosis degree [28][29][30] . Therefore, we speculated that the appearance of the vulnerable characteristics of the posterior circulation culprit plaque might be related to the metabolic factors of secondary diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with non-diabetic patients, diabetic patients had a signi cantly higher incidence of plaque enhancement, longer maximum plaque length, greater maximum plaque wall thickness, and increased luminal stenosis degree [28][29][30] . Therefore, we speculated that the appearance of the vulnerable characteristics of the posterior circulation culprit plaque might be related to the metabolic factors of secondary diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the following inclusion criteria were included: (1) age ≥18 years old, (2) ischemic stroke in the vertebrobasilar territory as identified by diffusion-weighted imaging (DWI)/T2-weighted imaging (T2WI)/CT, (3) 70–99% stenosis of the intracranial vertebral artery or basilar artery as confirmed by MRA, CTA, or DSA, and (4) two or more atherosclerotic risk factors including hypertension, hyperlipidemia, diabetes mellitus, obesity, and cigarette smoking. The definition of risk factor was the same as the previous protocol ( 22 ). Exclusion criteria were (1) coexistent >50% stenosis of the ipsilateral or bilateral extracranial vertebral artery; (2) evidence of cardio-embolism, such as atrial fibrillation, recent myocardial infarct within 4 weeks, mitral stenosis or prosthetic valve, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the parameters of the HRMRI multiple sequences were the same as the previous studies ( 22 , 25 ). The images were acquired by a coronal or axial view, which covered the intracranial vertebral artery and basilar artery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased vertebral artery (VA) difference, tortuosity and torsion as well as increased basilar artery (BA) curvature and tortuosity may cause a turbulent blood flow, which plays an important role in the pathogenesis of atherosclerosis [ 3 ]. Furthermore, it has been shown that the posterior circulation is much more susceptible to atherosclerosis in comparison with the anterior circulation [ 4 ]. These vertebrobasilar morphological indices have also been linked to peri-vertebrobasilar infarcts as risk factors and have indicated a directional and locational correlation [ 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%